PERANCANGAN APLIKASI PENJUALAN TAS PADA TOKO PELANGISHOP69 BERBASIS WEBSITE - Fatihah, Nasywa Rizki; Kurniawan, Fahmi; Fachri, Barany (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The era of digitalization of technological development is increasingly sophisticated and has become part of human needs, even in everyday life many people cannot be separated from technology, one of which is website technology. PelangiShop69 store, which is engaged in selling bags, is currently facing major challenges in terms of marketing and selling products. So far, the sales process has been carried out manually, which has resulted in limited market reach and difficulty in reaching wider consumers. This manual system relies on direct communication between sellers and buyers. This leads to a less efficient process, with a lack of promotion and easy access for a wider range of potential buyers. This is what encourages the author to overcome the problem by making research on bag sales based on website technology. The goal is to create a web-based bag sales application. It is hoped that the application created can successfully overcome the problems that occur and can make it easier for consumers and sales to communicate in website media and can also increase sales results and disseminate sales information. Keywords: Application, Sales, Bag, Consumer, Website Abstrak: Era digitalisasi perkembangan teknologi sudah semankin canggih dan menjadi bagian dari kebutuhan manusia, bahkan dalam kehidupan sehari-hari banyak orang yang tidak bisa lepas dari teknologi salah satunya teknologi website. Toko PelangiShop69 yang bergerak di bidang penjualan tas, saat ini menghadapi tantangan besar dalam hal pemasaran dan penjualan produk. Selama ini, proses penjualan dilakukan secara manual, yang mengakibatkan terbatasnya jangkauan pasar dan kesulitan dalam meraih konsumen lebih luas. Sistem manual ini mengandalkan komunikasi langsung antara penjual dan pembeli. Hal ini menyebabkan proses yang kurang efisien, dengan kurangnya promosi dan akses yang mudah bagi calon pembeli yang lebih luas. Hal ini yang mendorong penulis mengatasi masalah dengan membuat penelitian penjualan tas berbasis teknologi website. Tujuannya adalah untuk membuat sebuah aplikasi penjualan tas berbasis web. Diharapakan aplikasi yang dibuat berhasil mengatasi permasalahan yang terjadi dan dapat memudahkan pihak konsumen dan penjualan berkomunikasi dalam media website dan juga dapat meningkatkan hasil penjualan dan penyebaran informasi penjualan. Kata kunci: Aplikasi, Penjualan, Tas, Konsumen, Website